Effects of the Attributes Associated with Roadway Geometry, Traffic Volumes and Speeds on the Incidence of Accidents in a Mid-Size City - Guerrero Barbosa, Thomas Edison (2015)
Currently traffic accidents are the second cause of death, after homicides, in Colombia. Hence, government institutions require decision-making tools to identify and tackle the causes of traffic accidents. This research aims to determine the influence of factors related to roadway geometry and conditions, and traffic volumes and speeds on the frequency of accidents on the urban road network in the city of Ocaña (north of Santander). This study will take a methodological modeling approach, which will include measuring variables in the field, creating an accidents database, and conducting a subsequent analysis of the data by calibrating a model based on Poisson and Negative Binomial regressions. The results showed that variables such as road width, number of intersections, pavement type, traffic volumes (broken down into motorcycles, light, and heavy vehicles), and average driving speed (50th percentile) relate to accident rates.